SOCIAL-PSYCHOLOGICAL BASIS OF IDENTIFYING AND ELIMINATING STRESS IN ADOLESCENTS (Eureka Journal of Language, Culture & Social Change, 2026)
This article provides a scientific analysis of the causes and characteristics of stress in adolescence. It provides a theoretical basis for the impact of stress on the personality, emotional stability, and social adaptation of adolescents. It explores the concepts of stress theory, emotional development, personal crises, and adaptation from the perspective of adolescence. It also presents the foundations for refining and developing existing theoretical models for identifying and managing stress factors in the adolescent psyche. The study establishes a scientific basis for strengthening adolescent mental health, reducing emotional stress, and promoting social adaptation. An empirical study of stress factors in adolescents was conducted, presented in tables and diagrams. Psychological recommendations for stress relief were developed.
Keywords: teenager, adolescence, stress, stress factors, health, school, education, upbringing, emotional stress, personal crises, social adaptation, emotional stability, psychological balance